When unstable, growth is less pro-poor - Patrick Guillaumont; Catherine Korachais (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Macroeconomic instability has been increasingly considered as a factor lowering average income growth and, in this way, is a factor slowing down poverty reduction. But it can also result in slower poverty reduction for a given average rate of growth, due to poverty traps, often examined at the microeconomic level. Testing a model of poverty change on a panel of data for more than 80 countries from 1981 to 2005, we find that income instability results in a lower poverty reduction for a given growth. It reflects a distributional effect not fully captured by a change in the Gini coefficient.
Keywords: E32; I30; I32; O15; D31; O40; 330; income instability; poverty; inequality; economic growth; growth elasticity of poverty; poverty trap